Kidney Failure Due to Abdominal Compartment Syndrome Following Snakebite (Iranian Journal of Kidney Diseases, 2017)
Treatment of snakebite complications is challenging, as it is difficult to distinguish what kind of antivenins should be used. Kidney failure as a result of rhabdomyolysis or hemolysis may happen due to accumulated fluids that increase the pressure in the abdomen. This case report describes acute kidney failure probably due to intra-abdominal hypertension following an unknown bite.